Distribution of Mycobacterium avium subsp. paratuberculosis in a Subclinical Naturally Infected German Fleckvieh Bull. Issue 3 (15th December 2015) - Fechner, K.; Schäfer, J.; Wiegel, C.; Ludwig, J.; Münster, P.; Sharifi, A. R.; Wemheuer, W.; Czerny, C.‐P.
Summary: Although it has been known for years that Mycobacterium avium subsp. paratuberculosis (MAP) is detectable in the reproductive organs and semen of infected bulls, only few studies have been conducted on this topic worldwide. This study surveyed the MAP status of a bull, naturally infected due to close contact with its subclinically infected parents over a period of 4 years. From the age of 7 weeks to necropsy, faecal, blood and, after sexual maturity, semen samples were drawn repeatedly. Already at the first sampling day, MAP‐DNA was detected in faeces by semi‐nested PCR. True infection was confirmed by the detection of MAP‐DNA in blood at the age of 40 weeks. In total, MAP‐DNA was present in 25% faecal (34/139), 16% blood (23/140) and 5% semen (4/89) samples, including MAP‐free intervals of up to 9 weeks. MAP genome equivalents (MAP‐GE) of up to 6.3 × 10 6 /g faeces and 1.8 × 10 5 /ml blood were determined. Cultivation of MAP occurred only in three of 137 faecal and two of 109 blood, but never in semen samples. Over the whole period, the bull was a serological negative MAP shedder. During necropsy, 42 tissue samples were collected. Neither macroscopic nor histological lesions characteristic of a MAP infection were observed. Cultivation of MAP in tissue sections failed. However, MAP‐DNA was spread widely in the host, including in tissues of the lymphatic system (7/15), digestive tract (5/14) and the urogenital tract (5/9) with concentrations of up to 3.9 × 10 6 MAP‐GE/g tissue. The study highlighted the detection of MAP in male reproductive organs and semen. It supports the hypothesis that bulls may probably transmit MAP, at least under natural mating conditions. In artificial insemination, this might not be relevant, due to antibiotics included currently in semen extenders. However, the survivability of MAP in this microenvironment should be investigated in detail.